4 - Embattled Identity in Northeast Africa: A Comparative Essay - Bahru Zewde, (Afrika Zamani, 2022)
The Northeast African sub-region has been ridden with inter-state and intra- state conflicts since the beginning of the second half of the last century. And most of those conflicts have their roots in the clash of identities. In the pre- colonial period, language and religion constituted the major expressions of iden- tity. While Ethiopia and the Sudan evolved as a mosaic of diverse linguistic and religious groups, Somalia was characterized by relative homogeneity. Colonial rule created sharply defined international boundaries and partitioned some populations among two or more states. This state of affairs gave rise to irredentist movements, the most prominent two manifesting themselves in Eritrea and So- malia. Irredentism was abetted by the British policy of Greater Somalia, which led to a period of armed confrontation between Ethiopia and Somalia. Con- versely, in the Sudan, the British followed a deliberate policy of separating the South from the North; this was one of the factors behind the eruption of the civil war in the Sudan. While colonial rule might have sown the seeds for the numer- ous conflicts that have plagued the sub-region in the post-colonial period, the situation was aggravated by the assimilationist and integrationist ambitions of hegemonic regimes and the inability of liberation movements to aspire beyond the narrow confines of self-determination. The future salvation of the sub-re- gion seems to lie in the fostering of genuinely pluralistic societies that recognize the merits of multiple identities and aspire for a sub regional confederation rather than the continued veneration of the nation-state.